Free‐running 3D whole heart myocardial T 1 mapping with isotropic spatial resolution - Qi, Haikun; Jaubert, Olivier; Bustin, Aurelien; Cruz, Gastao; Chen, Huijun; Botnar, René; Prieto, Claudia (Magnetic resonance in medicine, 2019)
To develop a free-running (free-breathing, retrospective cardiac gating) 3D myocardial T mapping with isotropic spatial resolution. The free-running sequence is inversion recovery (IR)-prepared followed by continuous 3D golden angle radial data acquisition. 1D respiratory motion signal is extracted from the k-space center of all spokes and used to bin the k-space data into different respiratory states, enabling estimation and correction of 3D translational respiratory motion, whereas cardiac motion is recorded using electrocardiography and synchronized with data acquisition. 3D translational respiratory motion compensated T maps at diastole and systole were generated with 1.5 mm isotropic spatial resolution with low-rank inversion and high-dimensionality patch-based undersampled reconstruction. The technique was validated against conventional methods in phantom and 9 healthy subjects. Phantom results demonstrated good agreement (R = 0.99) of T estimation with reference method. Homogeneous systolic and diastolic 3D T maps were reconstructed from the proposed technique. Diastolic septal T estimated with the proposed method (1140 ± 36 ms) was comparable to the saturation recovery single-shot acquisition (SASHA) sequence (1153 ± 49 ms), but was higher than the modified Look-Locker inversion recovery (MOLLI) sequence (1037 ± 33 ms). Precision of the proposed method (42 ± 8 ms) was comparable to MOLLI (41 ± 7 ms) and improved with respect to SASHA (87 ± 19 ms). The proposed free-running whole heart T mapping method allows for reconstruction of isotropic resolution 3D T maps at different cardiac phases, serving as a promising tool for whole heart myocardial tissue characterization.